2023
DOI: 10.3389/fphar.2023.1157135
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of drugs for the treatment of psychiatric diseases in the pediatric population: focus on off-label use

Abstract: Psychotropics are increasingly used in pediatrics, often as off-label medicines. The guarantees of safety and efficacy are not always granted in clinical practice compared to adult authorised indications. A retrospective observational study was done to estimate the prevalence of psychotropic use in pediatric subjects of Catalonia (Spain). Anonymised data on dispensation of psychotropics to pediatric patients, demography and other related data were obtained by the local healthcare management for the period 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…In this way, dispensed antiepileptics have less risk to remain underestimated. Compared to previously reported rates of antiepileptics’ prevalence, Greece had similar ones to those reported in the Netherlands (3.7-4 per 1,000) ( van de Vrie-Hoekstra et al, 2008 ; Zito et al, 2008 ) and Germany (3.8 per 1,000) ( Zito et al, 2008 ), while in Spain (4.97 per 1,000) ( Pesiou et al, 2023 ) and the United Kingdom (7.3–8.69 per 1,000) the reported rates were higher. ( Ackers et al, 2007 ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this way, dispensed antiepileptics have less risk to remain underestimated. Compared to previously reported rates of antiepileptics’ prevalence, Greece had similar ones to those reported in the Netherlands (3.7-4 per 1,000) ( van de Vrie-Hoekstra et al, 2008 ; Zito et al, 2008 ) and Germany (3.8 per 1,000) ( Zito et al, 2008 ), while in Spain (4.97 per 1,000) ( Pesiou et al, 2023 ) and the United Kingdom (7.3–8.69 per 1,000) the reported rates were higher. ( Ackers et al, 2007 ).…”
Section: Discussionsupporting
confidence: 79%
“…The percentage of the overall off-label dispensations based on lack of pediatric recommendation in the SmPC was 5.5% in Greece; if the range of the recommended age was taken into consideration, then the percentage increased into 7.5%, with the younger populations mostly exposed to off-label dispensations as well as girls. Comparing with rates from other regions, Greece has similar rates with those observed in Spain (Pesiou et al, 2023), but much less exposure to off-label psychotropics than the one reported in Iceland (Zoëga et al, 2009).…”
Section: Use Of Psychotropics In Children and Adolescentssupporting
confidence: 60%
See 1 more Smart Citation
“…Antipsychotics (APs) were originally developed for the treatment of severe psychiatric disorders like schizophrenia and bipolar disorder but are now increasingly used for the treatment of restlessness, agitation, anxiety, sleep disorders, and other off-label indications (6). Particularly in children and adolescents, the off-label use of APs is common (7,8). Even though an off-label use is often unavoidable in pediatric care, it potentially increases the risk of adverse events (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%